Estudos biológicos e ecotoxicológicos da espécie Philodina roseola Ehrenberg, 1830 (Rotifera, Bdelloidea) - Moreira, Raquel Aparecida (2014)
In Brazil and other countries the agrochemical carbofurano is largely used, and can reach freshwaters and cause damages to non-target organisms. Rotifera dominates zooplankton communities of most freshwater ecosystems worldwide, both in number of species and density. In the present work biological and ecotoxicological studies in laboratory were carried out with the species Philodina roseola Ehrenberg, 1830 (Rotifera, Bdelloidea) regarding the main aspects of its biology: life cycle, filtration rates, ingestion and secondary production at 25 ± 1.0 °C, besides testing its sensitivity and performance as a test-organism for ecotoxicological studies. Also, a literature review regarding the use of rotifers as testorganisms in the evaluation of pesticides toxicity in freshwaters was carried out for the last three decades. Experiments were performed aiming to assess filtration and ingestion rates of P. roseola feeding on the microalgae Raphidocelis subcapitata at 7 different concentrations. The individual biomass (μg DW ind-1) and secondary production were determined. The main parameters obtained for P. roseola life cycle were: 23.88 ± 3.82 hours duration of embryonic development; 3.5 days generation time; 22.33 ± 2.29 eggs/female total mean fecundity and 23.0 days maximum longevity. Filtration rates varied between 2.715 and 6.615 ml ind-1d-1. Total mean individual secondary production was 0.285692 ± 0.055185 μg ind-1d-1 from which 73.42 ± 5.62 % was allocated into reproduction. P. roseola was an adequate test-organism for ecotoxicological studies considering the life cycle characteristics and response to the pesticide carbofurano with CE50 48-h values of 13.36 ± 2.63 mg L-1 and 89.32 ± 6.52 mg L-1 for the active ingredient and the commercial product, respectively. It was concluded that P. roseola has a fast development time, high metabolism as related to ingestion and filtration rates, high fecundity and moderate sensitivity to the tested pesticide. Studies on its functional response to other factors combinations and sensitivity to other toxicants should be performed.